The racketeer - Grisham, John. (New York : Bantam Books Trade Paperbacks, 2012)
When a federal judge and his secretary fail to appear for a scheduled trial and panicked clerks call for an FBI investigation, a harrowing murder case ensues and culminates in the imprisonment of a lawyer who imparts the story of who killed the judge and why.
Keywords: JUDGES -- CRIMES AGAINST; PRISONERS; MURDER -- INVESTIGATION; RACKETEERING; MURDER; JUDGES; LEGAL STORIES